Unintended Consequences : the Financial Assumptions and Economic Theory of Obamacare : the Patient Protection and Affordable Care Act - Thoene, Michael (Olsztyn Economic Journal, 2014)
This article examines the Patient Protection and Affordable Care Act (ACA,) often referred to colloquially as Obamacare, from a financial and economic perspective in order to analyze the potential efficacy of the system. Research was gathered pertaining to the stated objectives of the program, and economic theory was applied in order to reveal if the aims of the program are congruent with economic theory. It was found that the authors of the ACA did not anticipate or under-anticipated several economic effects of the legislation, which will hamper the implementation and effectiveness of the program. Furthermore, the economic theories employed by the Obama administration relied heavily upon classical economic theory, with little or no attention given to Transaction Cost Economics (TCE). Moreover, the law itself is overly complex and controversial due to a myriad of provisions added through the intercession of lobbyists from the healthcare, insurance and special interest sectors. The end result is that Americans may obtain a slightly improved healthcare system, but the United States will most likely still lag behind the rest of the industrialized world in many key health statistics.